2007
DOI: 10.1002/er.1294
|View full text |Cite
|
Sign up to set email alerts
|

Adiabatic capillary tube flow of carbon dioxide in a transcritical heat pump cycle

Abstract: SUMMARYFlow characteristics of an adiabatic capillary tube in a transcritical CO 2 heat pump system have been investigated employing the homogeneous model. The model is based on fundamental equations of mass, energy and momentum which are solved simultaneously. Two friction factor empirical correlations (Churchill, Lin et al., Int. J. Multiphase Flow 1991; 17(1):95-102) and four viscosity models (Mcadams, Cicchitti, Dukler and Lin) are comparatively used to investigate the flow characteristics. Choked conditio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
10
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
5
2

Relationship

3
4

Authors

Journals

citations
Cited by 37 publications
(11 citation statements)
references
References 19 publications
(17 reference statements)
1
10
0
Order By: Relevance
“…Parameters are chosen in such a way that there is no choking at the exit of the capillary tube. Onset of negative entropy change is used as a criterion to detect the choked flow condition in the capillary tube flow [9].…”
Section: Numerical Solutionmentioning
confidence: 99%
See 1 more Smart Citation
“…Parameters are chosen in such a way that there is no choking at the exit of the capillary tube. Onset of negative entropy change is used as a criterion to detect the choked flow condition in the capillary tube flow [9].…”
Section: Numerical Solutionmentioning
confidence: 99%
“…They concluded that a system operates closer to optimum conditions with capillary tube than a pre-fixed high pressure. Recently Agrawal and Bhattacharyya [9] presented the flow characteristics of an adiabatic capillary tube flow in the CO 2 transcritical heat pump cycle. Occurrence of choking, cause and effects, were also discussed in their analysis.…”
Section: Introductionmentioning
confidence: 99%
“…However, this simplified study did not include heat transfer, fluid flow and internal surface effects of the capillary tube. Agrawal and Bhattacharyya [19] presented characteristics and first law analysis of adiabatic capillary tube flow including choked flow in a transcritical heat pump cycle based on steady flow energy balance. Exergy analysis of a capillary tubebased transcritical carbon dioxide heat pump system for simultaneous cooling and heating applications including heat transfer and fluid flow effects in the heat exchangers have not been reported yet.…”
Section: Introductionmentioning
confidence: 99%
“…Agrawal and Bhattacharyya [11] investigated flow characteristics of an adiabatic capillary tube in a transcritical carbon dioxide heat pump system. Aprea and Maiorino [12] described experiments comparing a commercial available R134a refrigeration plant subjected to a cold store and a proto type carbon dioxide system working as a classical 'spilt-system' to cool air in residential applications in a transcritical cycle.…”
Section: Introductionmentioning
confidence: 99%